2021
DOI: 10.3390/ijerph18041920
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Workplace on Work Participation and Sick Leave after a Terrorist Attack: A Qualitative Study

Abstract: Returning to work after large-scale traumatic events is desirable for employees, their organization, and society. The aim of the present study was to identify work-related factors that are perceived as important for work participation versus sick leave after a terrorist attack. We conducted in-depth interviews of 98 employees in the Norwegian governmental ministries that were the target of the 2011 Oslo bombing. Participants were randomly selected from 2519 employees who had responded to a web-based survey. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Further, we propose two reasons that explain why telework satisfaction is expected to increase the employees’ levels of wellbeing. First, in times of crisis, working can become a coping strategy to adjust to the new situation (Kirchner et al, 2021 ) and to promote mental health and resilience (Heir et al, 2021 ). In their study after the Oslo terrorist attack in 2011, Heir et al ( 2021 ) found that work provided employees with a sense of cohesion, supportive management, and peer support, thus enhancing their wellbeing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we propose two reasons that explain why telework satisfaction is expected to increase the employees’ levels of wellbeing. First, in times of crisis, working can become a coping strategy to adjust to the new situation (Kirchner et al, 2021 ) and to promote mental health and resilience (Heir et al, 2021 ). In their study after the Oslo terrorist attack in 2011, Heir et al ( 2021 ) found that work provided employees with a sense of cohesion, supportive management, and peer support, thus enhancing their wellbeing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, in times of crisis, working can become a coping strategy to adjust to the new situation (Kirchner et al, 2021 ) and to promote mental health and resilience (Heir et al, 2021 ). In their study after the Oslo terrorist attack in 2011, Heir et al ( 2021 ) found that work provided employees with a sense of cohesion, supportive management, and peer support, thus enhancing their wellbeing. In face of COVID-19, the organizations’ facilitation of adequate telework conditions may have helped employees to cope with the new situation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the long run, emotions can manifest themselves in job satisfaction or work productivity ( 13 ). Thus, several factors could have influenced employees' perception of predictability and role expectations, such as relocations, loss of infrastructure and personal property ( 14 ), increase in sick leave ( 15 ), acquired post-traumatic stress reactions ( 10 ), concerns about safety at work ( 16 ), experiences of high work demand ( 17 ), and disagreement in the workforce about who deserved relief and support the most ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Perceptions of the psychosocial work environment is important for maintaining health and productivity after a workplace disaster ( 2 4 , 17 ). Our findings that previous levels of perceived predictability and role expectations were maintained after a terrorist attack are in that sense a positive message with important implications.…”
Section: Discussionmentioning
confidence: 99%
“…High-quality team leadership has been shown to be significantly associated with a lowered risk of subsequent mental distress [33]. Good team leadership plays an important role in employee health and well-being as well as reducing burnout [34]. It is also an essential antecedent of occupational safety; rule-oriented leadership that formulates plans for future operations collaboratively with the workers improves the workers' motivation to comply with safety regulations and to participate in safety-promoting activities [35].…”
Section: Comparisons With the Literaturementioning
confidence: 99%